Intelligent manufacturing, green technological innovation and environmental pollution - Yang Shen; Xiuwu Zhang (Journal of Innovation & Knowledge (JIK), 2023)
Intelligent manufacturing offers opportunities for green technology innovation at a low cost, helps eliminate outdated equipment, and improves pollution efficiency, which is essential for environmental protection. From the perspective of the industrial sector, based on the data of 269 Chinese cities, this study empirically examines the impacts of intelligent manufacturing on ecological environment using the fixed effect model and unconditional quantile model. The research results show that intelligent manufacturing can significantly reduce the concentration of PM2.5 in the air and environmental pollution by optimizing resource allocation during production and operation. The results of the external mechanism show that green technological innovation plays a positive mediating role in the impact mechanism of intelligent manufacturing to improve air quality. The marginal impact of intelligent manufacturing on environmental pollution is nonlinear, and the main trend is the M-type distribution trend of increasing first, then decreasing, and then rising. In particular, intelligent manufacturing has a greater welfare effect on the ecological environment at the lower quantiles. The results provide a viable path for the government to actively plan a strategic layout to improve the ecological environment and achieving the goal of high-quality economic development.
Keywords: O33; Q51; Q55; 650; Air pollution; Green technological innovation; Industrial robots; Intelligent technology; Total factor productivity; Unconditional quantile regression model